Peran Brand Ambassador Dalam Membangun Informasi Di Media Sosial Tentang Museum - Rasyid, Budi Mulya (JURNAL DESTINASI PARIWISATA, 2024)
Museums are a source of learning for students and the general public. The problem in the digital age is that visitors have access to so much information without having to go anywhere, that boring museum exhibitions and promotions can turn them off. The use of social media as a means of promotion and selecting brand ambassadors plays an important role in increasing wider awareness of the museum. Through good and interesting promotional activities, museums build a good brand image to attract visitors. The purpose of this literature review article is to explain the importance of museum promotion in the digital era through the use of various social media platforms and the selection of brand ambassadors. Descriptive analysis and detailed discussion of the situation in the field are used to strengthen the discussion. Keywords: Museum, Digital, Brand Ambassador, Promosi, Informasi